TIPOLOGI ATAP PADA ARSITEKTUR VERNAKULAR DI SUMATERA SELATAN - Zuber Angkasa Wazir (Jurnal Koridor, 2018)
The development of new urbanism paradigm in the world today, has been reminded of the importance of vernacular architecture in urban planning.. It would be advantageous for areas with high ethnic diversity as South Sumatra. This study aims to inventory the vernacular house typology in South Sumatra. Methods of study is to examine the vernacular houses of all ethnicities in South Sumatra (29 ethnicity) plus two ethnic from neighboring provinces (Kubu and Lambak). The study found 18 different types of houses, and also found that the typology of the roof consists of a limas roof, pelana roof, and a perisai roof. The variety of roof reflects the high ethnic mobilization in South Sumatra. Even so, as a result of acculturation that occurs in these dynamics, the variety is found only on the shape of the roof, while the other part of the building does not have a clear marker of difference. Implications of the New Urbanism presented in the design of contemporary urban planning in South Sumatra.